A transient ischemic environment induces reversible compaction of chromatin - Kirmes, Ina Caroline; Prakash, Kirti; Ma, Dongyu; Cremer, Christoph (Genome biology, 2015)
Cells detect and adapt to hypoxic and nutritional stress through immediate transcriptional, translational and metabolic responses. The environmental effects of ischemia on chromatin nanostructure were investigated using single molecule localization microscopy of DNA binding dyes and of acetylated histones, by the sensitivity of chromatin to digestion with DNAseI, and by fluorescence recovery after photobleaching (FRAP) of core and linker histones.